Chondrocytes From Osteoarthritic and Chondrocalcinosis Cartilage Represent Different Phenotypes - Meyer, Franziska; Dittmann, Annalena; Kornak, Uwe; Herbster, Maria; Pap, Thomas; Lohmann, Christoph H.; Bertrand, Jessica (Frontiers in Cell and Developmental Biology, 2021)
Basic calcium phosphate (BCP)-based calcification of cartilage is a common finding during osteoarthritis (OA) and is directly linked to the severity of the disease and hypertrophic differentiation of chondrocytes. Chondrocalcinosis (CC) is associated with calcium pyrophosphate dihydrate (CPPD) deposition disease in the joint inducing OA-like symptoms. There is only little knowledge about the effect of CPPD crystals on chondrocytes and the signaling pathways involved in their generation. The aim of this study was to investigate the chondrocyte phenotype in CC cartilage and the effect of CPPD crystals on chondrocytes. Cartilage samples of patients with CC, patients with severe OA, and healthy donors were included in this study. The presence of CC was evaluated using standard X-ray pictures, as well as von Kossa staining of cartilage sections. OA severity was evaluated using the Chambers Score on cartilage sections, as well as the radiological Kellgren–Lawrence Score. Patients with radiologically detectable CC presented calcification mainly on the cartilage surface, whereas OA patients showed calcification mainly in the pericellular matrix of hypertrophic chondrocytes. OA cartilage exhibited increased levels of collagen X and matrix metalloproteinase 13 (MMP13) compared with CC and healthy cartilage. This observation was confirmed by qRT-PCR using cartilage samples. No relevant influence of CPPD crystals on hypertrophic marker genes was observed in vitro, whereas BCP crystals significantly induced hypertrophic differentiation of chondrocytes. Interestingly, we observed an increased expression of p16 and p21 in cartilage samples of CC patients compared with OA patients and healthy controls, indicating cellular senescence. To investigate whether CPPD crystals were sufficient to induce senescence, we incubated chondrocytes with BCP and CPPD crystals and quantified senescence using β-gal staining. No significant difference was observed for the staining, but an increase of p16 expression was observed after 10 days of culture. Primary chondrocytes from CC patients produced CPPD crystals in culture. This phenotype was stabilized by mitomycin C-induced senescence. Healthy and OA chondrocytes did not exhibit this phenotype. BCP and CPPD crystals seem to be associated with two different chondrocyte phenotypes. Whereas BCP deposition is associated with chondrocyte hypertrophy, CPPD deposition is associated with cellular senescence.